2010
DOI: 10.4236/eng.2010.211116
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lauroyl Glutamine on Biodegradation of Lubricating Oil and Simulation of Biodegradation Kinetics

Abstract: Small amount of lauroyl glutamine was incorporated into HVI 350 mineral lubricating oil and the biodegradabilities of neat oil and the formulated oil in soils were evaluated. Thereafter, the biodegradation rate equations for the two lubricating oils were simulated based on the exponential model. The results indicated that lauroyl glutamine effectively promoted biodegradation of HVI 350 mineral lubricating oil. Under given test conditions, the exponential model well fitted the biodegradation of lubricating oils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…22 However, biodegradability is a system concept including comprehensive influencing factors, and research works have demonstrated that oil–water interfacial tensions is one of the factors. 23 It is known that rapeseed oil is a lubricant with excellent biodegradability, but the incorporation of BNS1 or BNS2 would most probably affect the oil–water interfacial tensions, which would alter the oil–water interfacial area and thus affecting the microorganisms to metabolize lubricants. As can be seen from the structure of the two additives, BNS2 might be more helpful to increase the oil–water interfacial area and promote microorganisms to better metabolize a lubricant due to its longer chain structures, while for BNS1, it is vice versa.…”
Section: Resultsmentioning
confidence: 99%
“…22 However, biodegradability is a system concept including comprehensive influencing factors, and research works have demonstrated that oil–water interfacial tensions is one of the factors. 23 It is known that rapeseed oil is a lubricant with excellent biodegradability, but the incorporation of BNS1 or BNS2 would most probably affect the oil–water interfacial tensions, which would alter the oil–water interfacial area and thus affecting the microorganisms to metabolize lubricants. As can be seen from the structure of the two additives, BNS2 might be more helpful to increase the oil–water interfacial area and promote microorganisms to better metabolize a lubricant due to its longer chain structures, while for BNS1, it is vice versa.…”
Section: Resultsmentioning
confidence: 99%
“…In order to reduce the number of such additives, the demand of multifunctional additives (MFA) is quite high. Conventional MFAs including zinc dialkyldithiophosphate (ZnDDP), sulfonte, mannich base, etc are not biodegradable, and hence, maintaining the biodegradable nature of biolubes in the presence of an additive is one of the main challenges. This aspect can be exemplified using the case of ZnDDP, which works well in biolubricant base but suffers from the limitations related with environmental concerns arising from S, P, and metal atoms. An additional problem with using ZnDDP is the poisoning of catalytic convertors in automobiles .…”
Section: Introductionmentioning
confidence: 99%